Application of acute pre-exercise partial-body cryotherapy promotes jump performance, salivary-amylase and athlete readiness - M. Partridge, Emily; Cooke, Julie; J. McKune, Andrew; B. Pyne, David (Biology of Sport, 2022)
This study aimed to evaluate the application of a single pre-exercise bout of partial-body cryotherapy (PBC) to augment jump performance, salivary biomarkers and self-reported performance readiness. Twelve male rugby union players (age 20.7 ± 3.2 yr; body mass 93.1 ± 13.9 kg; mean ± SD) were exposed to PBC for 3 min at –140°C or control condition prior to a pre-post series of loaded countermovement jumps (CMJ), salivary biomarker samples and performance readiness questionnaires. PBC elicited a moderately greater improvement in CMJ velocity of +4.7 ± 3.5% (mean ± 90% confidence limits) from baseline to 15 min in comparison with a -1.9 ± 4.8% mean difference in the control condition. The mean change in concentration of salivary α-amylase at 15 min was substantially increased by +131 ± 109% after PBC exposure, compared to a -4.2 ± 42% decrease in the control. Salivary testosterone concentrations were unclear at all timepoints in both the PBC and control interventions. Self-reported perceptions of overall performance readiness indicated small to moderate increases in mental fatigue, mood, muscle soreness and overall questionnaire score after PBC compared to control with a higher score more favourable for performance. The application of pre-exercise PBC can elicit favourable outcomes in controlled physical performance tests and holds promise to be applied to training or competition settings.